Publication Phishing: A Growing Challenge For Researchers And Scientific Societies - Sorooshian, Shahryar (Current Science Association, 2016)
Publication phishing has the potential to develop further into a serious gainful enterprise if effective security measures are not in place. Be that as it may, there is growing concern over the erosion of users’ trust towards journals, conferences and other channels of publication stemming from the rise in scam cases involving users’ money, research articles and personal identifications. Phishing is becoming a major issue for users and will be making an ever greater and prominent issue for good scientific societies who need to devise anti-journal hijacking measures to mitigate the impacts of phishing to their operations. Researchers and scientific societies need to design adequate technical security systems to mitigate phishing threat to users. This note highlights some issues and basic steps to anti-phishing educators and scientific societies to ensure the viability of anti-phishing initiatives